Management of the Rural Tourism Cluster Based on Cash Flows’ Economic-Mathematical Model - Миронов Юрій Богданович; Svatiuk Oksana; Popadynets Nazariy; Leshko Khrystyna; Malska Marta; Popovych Daria; Petyk Liubov; Palasevych Mykola (Vytautas Magnus University, 2023)
The management of a rural tourism cluster based on an economic-mathematical model stipulates the use of mathematical modeling methods to optimize the economic parameters of the cluster’s activity. Therefore, the practical aspects of the application of a system approach to the development and improvement of the management system in a rural tourism cluster are substantiated. The article aims to develop an economic-mathematical model for the optimization of the management of the rural tourism cluster parameters. The model uses the Kalman filter and deterministic feedback to evaluate the state of the dynamic system based on observations. The developed models and the management optimization algorithm are synthesized in the automatized information-analytical management subsystem. The typical list of business processes in the activity of a rural tourism cluster is characterized to specify managerial actions and improve their efficiency and performance. The ways of the algorithm’s integration into the automatized information-analytical management subsystem are outlined. Overall, the article offers the method of optimization of rural tourism cluster management based on mathematical modeling and management optimization.
Keywords: management; rural tourism cluster; economic-mathematical model; cash flows